STYLE OF POLITICAL PREACHING OF IMAM MALIK BIN ANAS ( AMAM OF DARELHIJRAH ) THROUGH HIS CORRESP ONDENCE WITH CALIPH HAROON ELRASHEED AND HIS MINISTER YEHYA BIN KHALID AL – BARMAKI - HUSSEIN , MOHAMMED (Islamic Sciences Journal, 2023)
Political characters in Islam are outnumbered, however their cultural sources varries according to their cultural resources and ethnic affiliation. When men of religion involve in politics, policy will wear a religions cloak So it is a legitimate policy under the religion because it is part of religion as it is the case in Imam Malik bin Anas through his trea tise in Sunnahs, preaches, Literatures for Haroon elrasheed and his minister yahya bin khalid Al-Barmaki in an attempt to create the core of concepts of politics and governance in Islam In order to support the Caliphate Foundation against competing cultures on the ground.